PENGARUH KETIDAKPASTIAN BLIND BOX TERHADAP NIAT BELI: MEDIASI NILAI, MODERASI DARING - Phangkawira, Stanley (GEMAH RIPAH: Jurnal Bisnis, 2025)
This study investigates the effect of product uncertainty in blind box purchases on consumers’ purchase intention, incorporating perceived value as a mediating variable and online purchase as a moderating variable. Drawing on the theory of perceived value, the research examines how uncertainty influences functional, emotional, and social values, which in turn affect purchase intention. A quantitative approach was employed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) on data collected from 73 respondents familiar with blind box products. The findings show that uncertainty significantly affects perceived value, which mediates the relationship with purchase intention. However, the moderating role of online purchase was found to be statistically insignificant, indicating that the purchase context did not substantially alter the effect pathways. These results provide insights into how consumers respond to uncertainty in blind box products and contribute to the growing literature on perceived value and purchase behavior in uncertain product environments.